Factors affecting quality of goat’s milk yogurt - Sandulachi, Elisaveta; Bulgaru, Viorica (Advances in Social Sciences Research Journal, 2019)
A comparative study of the quality and nutritional value of Moldova’s cow and goat milk is presented. Organoleptic properties (taste, odor, appearance, color), physicochemical indicators (acidity, fat content, protein, viscosity, Q10 value et at.) microbiological indices (total number of colony forming units, Listeria monocytogenes, Staphylococcal Enterotoxin, Salmonella, Enterobacteriaceae, Bacillus cereus), the presence of antibiotics and preservatives. The study includes the microbiological analysis of milk according to the season. Starter cultures were tested for temperature, light, O2 access. The article presents and argues the factors determining the quality of cow milk and goat milk, the technological scheme for the manufacture of yogurt by the thermostat method, and its quality indexes (organoleptic, physico-chemical and microbiological).